Características fotossintéticas de genótipos de capim-elefante anão (Pennisetum purpureum Schum.), em estresse hídrico - Do Carmo Araújo, Saulo Alberto; Vasquez, Hernan Maldonado; Campostrini, Eliemar; Netto, Alena Torres; Deminicis, Bruno Borges; Da Silva Lima, Érico [UNESP] (Universidade Estadual de Maringa, 2010)
The experiment was carried out aiming to evaluate the gas exchange of dwarf elephant grass genotypes under different hydric conditions, in a randomized design with three replications. Genotypes of dwarf elephant grass (Mott, CNPGL 94-34-3 and CNPGL 92-198-7) were analyzed under two hydric conditions: irrigated (I) and non-irrigated (NI). Differences between treatments I and NI were observed for all genotypes for photosynthesis, stomatal conductance, transpiration and water vapor pressure deficit. Genotype CNPGL 94-34-3 presented highest tolerance to hydric stress, followed by Mott and CNPGL 92-198-7 genotypes. All genotypes presented high photosynthetic rate, under ideal conditions of soil humidity, thus characterizing the analyzed dwarf elephant grass genotypes as plants with high photosynthetic efficiency.
Photosynthetic characteristics of dwarf elephant grass (Pennisetum purpureum Schum.) genotypes under different hydric conditions
Keywords: Photoinhibition; Photosynthesis; Stomatal conductance; Transpiration; Vapor pressure deficit; Pennisetum glaucum; Pennisetum purpureum